Atmospheric levels, distribution, sources, correlation with meteorological parameters and other pollutants and health risk of PAHs bound in PM2.5 and PM10 in Burgas, Bulgaria – a case study. Issue 4 (21st March 2022) - Naydenova, St.; Veli, A.; Mustafa, Z.; Hudai, S.; Hristova, E.; Gonsalvesh-Musakova, L.
Abstract: The quality of atmospheric air of Burgas city, Bulgaria was analyzed in relation to PAHs in two particulate matter fractions – 2.5 μm and 10 μm. It was found that PAHs registered in PM10 represent entirely the ones registered in PM2.5 – an indication that the particulate PAHs in ambient air of Burgas for the sampling period are associated with the fine PM fraction. The PAH compounds with highest concentrations are mainly associated with coal combustion, diesel and gasoline vehicle and biomass burning, which is further confirmed by the calculated diagnostic ratios. The combustion-derived PAHs represent on average 86.6 ± 2.8% of total PAHs concentration. The linear regression analysis showed strong and statistically meaningful correlations between PM fractions and PAHs indicating the influence of similar local events and emission sources of pollution. PM2.5 or PM10 relationships with PAHs were significant but lower correlation coefficients were observed for low-molecular weight (LMW) PAHs in comparison to middle-molecular weight (MMW) and higher-molecular weight (HMW) PAHs, due to their lower presence in particulates and higher partition in gaseous atmospheric phase. Further significant correlations were found with wind speed, solar radiation and atmospheric pressure as well as NO2 and O3 ambient concentration. The calculated excess cancer risks are twice as much as acceptable limit.